EKTIVITAS MODEL PEMBELAJARAN TSTS (TWO STAY TWO STRAY) TERHADAP HASIL BELAJAR IPA SISWA SD - Pratama, I Putu Windu (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
This study aimed to determine the Effectiveness of the Two Stay Two Stray Learning Model on Science Learning Outcomes of Elementary School Students. This research approach is descriptive quantitative using meta-analysis, through data collection activities by searching for articles through google scholar search or google scholar. The steps in this meta-analysis research are as follows: (1) determine and study the research topics to be summarized, (2) find and collect a number of predetermined topics and select them, (3) calculate the effect size, and (4) attract conclusions and interpret the results of the meta-analysis research. The characteristics of the subject of this study are articles related to the Two Stay Two Stray learning model on the national science learning outcomes of elementary school students, which have been recorded in the last five years from 2015 to 2020, the articles collected have the following similarities: 1) articles made by students of school education study programs, teachers in elementary schools, and researchers in the field of primary school education (2) using experimental research methods that have been implemented in elementary schools, (3) articles are quantitative research using the t test hypothesis test and meet the effect size data, and (4) the coverage of the research sample is carried out in the Indonesian region. Research conducted by Pratiwi, Suartama, and Sumantri (2016) The effect of the Two Stay Two Stray Cooperative Model on Science Learning Outcomes has a very high effectiveness value, the results of this study are supported by previous research conducted by Widiatmika and Ismawati (2012) regarding the application of the Model Cooperative Learning Type Two Stay Two Stray which explains that the TSTS Type Cooperative Learning Model can improve student learning outcomes